Setting the Table: Majority Party Effects in the United States Senate. Issue 1 (2nd January 2016) - King, Aaron S.; Orlando, Frank J.; Rohde, David
Abstract : This article joins the growing tide of research that studies party effects in the United States Senate. Previous work has shown that certain procedural tools disproportionately advantage the majority party at the expense of the minority. We build on this research by exploiting a new dataset that allows us to study motions to table amendments from the 91st to the 111th Congress. By examining the success of these motions, analyzing the voting calculus of individual senators on procedural and substantive votes, and simulating the aggregate impact of this tool, we provide some of the strongest evidence to date that political parties (and the majority party in particular) influence the legislative process and policy outcomes in the Senate. Our findings stand in stark contrast to the traditional vision of the Senate as an individualistic body.